2010
DOI: 10.1074/jbc.m110.146092
|View full text |Cite
|
Sign up to set email alerts
|

Binding and Functional Properties of Five Extrinsic Proteins in Oxygen-evolving Photosystem II from a Marine Centric Diatom, Chaetoceros gracilis*

Abstract: Oxygen-evolving photosystem II (PSII) isolated from a marine centric diatom, Chaetoceros gracilis, contains a novel extrinsic protein (Psb31) in addition to four red algal type extrinsic proteins of PsbO, PsbQ , PsbV, and PsbU. In this study, the five extrinsic proteins were purified from alkaline Tris extracts of the diatom PSII by anion and cation exchange chromatographic columns at different pH values. Reconstitution experiments in various combinations with the purified extrinsic proteins showed that PsbO, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
37
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(43 citation statements)
references
References 43 publications
6
37
0
Order By: Relevance
“…In cyanobacteria, there are also homologs of PsbP and PsbQ, termed CyanoP and CyanoQ, respectively (7,8), but these have not yet been included in current structural models. Red algae and diatoms have their own specific lumenally bound extrinsic subunits, such as PsbQЈ and Psb31 (9,10). Interestingly, the PsbP and PsbQ proteins in green plants seem to have evolved from CyanoP and CyanoQ in cyanobacteria, although considerable genetic and functional modifications have occurred to generate the forms of these proteins seen in eukaryotes today (11).…”
Section: Photosystem II (Psii)mentioning
confidence: 99%
“…In cyanobacteria, there are also homologs of PsbP and PsbQ, termed CyanoP and CyanoQ, respectively (7,8), but these have not yet been included in current structural models. Red algae and diatoms have their own specific lumenally bound extrinsic subunits, such as PsbQЈ and Psb31 (9,10). Interestingly, the PsbP and PsbQ proteins in green plants seem to have evolved from CyanoP and CyanoQ in cyanobacteria, although considerable genetic and functional modifications have occurred to generate the forms of these proteins seen in eukaryotes today (11).…”
Section: Photosystem II (Psii)mentioning
confidence: 99%
“…The other two subunits, PsbU and PsbV, are present in PSII of cyanobacteria and most eukaryotic algae including red algae, diatom etc (11,(13)(14)(15), whereas they are replaced by two nonhomologous subunits, PsbQ (17 kDa) and PsbP (23 kDa), in the green lineage including green algae and higher plants (11,(15)(16)(17)(18)(19)(20). Proteins homologous to PsbQ and PsbP were also found in cyanobacteria (cyanoPsbQ and cyano-PsbP) (15)(16)(17)(18)(19)(20)(21), as well as some eukaryotic algae such as diatom (14). The cyanoQ and cyanoP, however, have been lost in the purified cyanobacterial PSII, and no crystal structure of PSII from eukaryotic organisms has been solved; therefore, the association pattern of these proteins with PSII is not clear.…”
mentioning
confidence: 99%
“…This may be because PsbP and PsbQ proteins do not directly, but do bind to PSII complex only by PsbO that binds to the PSII core complex. 31 So the release of PsbP and PsbQ proteins is not or less influenced by ROS generated in the PSII core complex and may be initiated just by absorption of visible light. Actually, previous study showed that PsbP and PsbQ proteins released more easily than PsbO protein did under high light condition.…”
Section: Discussionmentioning
confidence: 99%